Preoperative Evaluation of Oswestry Disability Index in Lumbar Spinal Stenosis : New Evidence of Time Independence of Variation Up to 1 Year - Hatakka, Juho; Pernaa, Katri; Kostensalo, Joel; Mäkelä, Keijo; Laaksonen, Inari (International Society for the Advancement of Spine Surgery, 2025)
Background: The Oswestry Disability Index (ODI) is a well-validated and widely used patient-reported outcome instrument to evaluate lumbar spinal stenosis (LSS) patients’ treatment outcomes. The objective of the present study was to determine long the average interval between 2 preoperative measurements can be before a clinically significant difference of 10 points or more might appear. Methods: This was a retrospective observational study utilizing prospectively collected data from a single university hospital database, which was compatible with the national registry. One hundred and four surgically treated LSS patients were included in this observational study using systematic sampling. The preoperative ODI score was obtained at 2 timepoints. The 2-month mark as a potential turning point was of special interest, as the registry in question excludes preoperative data as outdated if the data are older than 2 months. Possible time dependence of the change in ODI scores was explored using a linear mixed-effects model with ODI as the dependent variable and interval length, sex, age, body mass index (BMI), and the presence of a concomitant disease as fixed effects. Results: The mean ODI score was 41.7 points (SD = 16.0) at the first and 41.1 points (SD = 15.5) at the second measurement. Mean time between the ODI scores was 74 days (range 8–361). On average, ODI changed by 9.17 points (SD = 7.16) between the 2 measurements, increasing for 48 patients, remaining unchanged for 9 patients, and decreasing for 47 patients. The arithmetic mean of the changes was −0.60 points and the median was 0.00 points. The estimated change in the population mean was −0.0005 points/day (95% CI [−0.022, 0.022], P = 0.97), meaning that we have strong evidence that the change in the mean is not clinically significant for up to 15 months (95% CI between ±10 points). Furthermore, no evidence was found that age, sex, BMI, or concomitant diseases were associated with the change of ODI score over time. Furthermore, the probability to observe a clinically significant change in a patient did not depend on the number of days between the 2 measurements (OR 1.003, 95% CI [0.997, 1.010], P = 0.30). Variance in ODI change did not grow over time. Conclusions: The probability of observing a clinically significant differences does not depend on the length of the observation interval, and ODI scores can be considered equally reliable for a significantly longer time than 2 months, even up to 1 year. Clinical Relevance: Preoperative ODI scores do not lose reliability up to 1 year in patients undergoing operatively treatment for LSS. Level of Evidence: 3.
Keywords: spien; lumbar spinal stenosis; patient reported outcome; oswestry disability index; ODI score; registry study